Nocturnal enuresis and sleep disordered breathing in primary school children: Potential implications. Issue 11 (11th September 2018) - Wada, Hiroo; Kimura, Manami; Tajima, Tomokazu; Shirahama, Ryutaro; Suzuki, Yohei; Suzuki, Yuka; Hayashi, Toshinari; Maruyama, Koutatsu; Endo, Motoki; Sakamoto, Naoko; Ikeda, Ai; Gozal, David; et al.
Abstract: Introduction: The association between nocturnal enuresis (NE) and sleep disordered breathing (SDB) has been repeatedly reported, but has primarily been focused on clinical cohorts. The purpose of this study, was to assess whether SDB‐related symptoms such as snoring and unrefreshing sleep in the morning are associated with NE in a large‐scale community school‐based survey. Methods: A cross‐sectional assessment using a standard questionnaire was conducted on nearly 20 000 primary school children (5‐12 years old) in Matsuyama, Japan. Associations between NE and the frequencies of snoring and unrefreshing sleep were evaluated using multivariate logistic and regression analyses. Results: Multivariate adjusted odds ratios (95% confidence intervals) for enuresis were 1.21 (1.04 to 1.40) and 1.36 (1.07 to 1.73) in boys who snored 1 or 2 nights per week and ≥3 nights per week, respectively ( P for trend <0.0001). Those for enuresis were 1.67 (1.41 to 1.99) and 1.96 (1.63 to 2.36) in boys who showed unrefreshing sleep 1 or 2 nights per week and ≥3 nights per week, respectively ( P for trend <0.0001). Significant associations between NE and snoring frequency emerged among children who did not report unrefreshing sleep ( P ‐trend for boys and girls were <0.0001 and <0.01, respectively), while significant associations between NE and frequency of unrefreshing sleep were detected among children who snored ≥1 nights per week ( P for trend >0.1). Conclusions: The pathogenic mechanisms linking snoring and unrefreshing sleep to increased risk of NE are unknown. However, snoring, a surrogate reporter of SDB, is associated with increased urine production, while unrefreshing sleep may result from disrupted sleep facilitating increased sleep pressure and elevated arousal thresholds. Thus, both SDB and unrefreshing sleep are potential independent risk factors of NE in school age children.